2014
DOI: 10.1103/physrevc.90.061604
|View full text |Cite
|
Sign up to set email alerts
|

Decay and structure of the Hoyle state

Abstract: The first $0^+$ resonant state of the $^{12}$C nucleus ${}^{12}$C$(0_2^+)$, so called the Hoyle state, is investigated in a three-$\alpha$-particle (3-$\alpha$) model. A wave function for the photodisintegration reaction of a $^{12}$C bound state to 3-$\alpha$ final states is defined and calculated by the Faddeev three-body formalism, in which three-body bound- and continuum states are treated consistently. From the wave function at the Hoyle state energy, I calculated distributions of outgoing $\alpha$-partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(107 citation statements)
references
References 25 publications
6
100
1
Order By: Relevance
“…system above the 3α threshold. This is an extension of recent works [5,6], in which 3α continuum states up to E = 0.6 MeV were studied to calculate the reaction rate of the triple-α process at stellar temperature T ∼ 10 9 K, and clarify the decay mode of the Hoyle state.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…system above the 3α threshold. This is an extension of recent works [5,6], in which 3α continuum states up to E = 0.6 MeV were studied to calculate the reaction rate of the triple-α process at stellar temperature T ∼ 10 9 K, and clarify the decay mode of the Hoyle state.…”
Section: Introductionmentioning
confidence: 74%
“…In Ref. [6], it was shown that the decay of the Hoyle state is dominated by a sequential decay (SD) process, in which the decay occurs in two steps: first 3 α-particles separate to 2-α resonant state, 8 Be(0 Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A precise answer is obtained from the calculation of the bosonic occupation numbers which have been obtained in three different works [23,28,29] with very similar results. The ones of [29] are displayed in Figure 7.…”
mentioning
confidence: 94%
“…For the microscopic description of the Hoyle state several approaches have been put forward in the past [14,16,17,19,[21][22][23]. However, only the following, so-called THSR wave function (according to the authors Tohsaki, Horiuchi, Schuck, Roepke) which was proposed in [1] concentrates on the α particle condensation aspect (the spin-isospin part is not written out)…”
Section: Finite Nuclei and The Thsr Approach The Hoyle State In 12 Cmentioning
confidence: 99%